A review of the idiodynamic method as an emerging research method for the investigation of affective variables in second language acquisition - Lu, Miaoyan (Frontiers in Psychology, 2022)
Recent years have witnessed the influence of the complex dynamic systems theory (CDST) in the field of second language acquisition (SLA). Thus, new research methods have also been introduced to meet the requirements of investigating the dynamic nature of learner-related factors including L2 affective variables. Among the innovative quantitative research methods which is compatible with the CDST is the idiodynamic method, the application of which is on the rise in SLA research. In this paper, an overall introduction to the idiodynamic method is presented first, followed by a review of the existing literature in SLA studies. Then, it is discussed why this innovative research method is suitable to investigate the dynamic nature of L2 learners’ affective variables in the complex network of classroom learning. Also, several relevant research questions that can potentially be formulated and answered using the idiodynamic method are discussed. The paper ends with conclusive remarks on the need for more extensive use of innovative CDST-compatible research methods such as the idiodynamic method in the prospective SLA line of inquiry.